2006
DOI: 10.5551/jat.13.123
|View full text |Cite
|
Sign up to set email alerts
|

Statins: Beneficial or Adverse for Glucose Metabolism

Abstract: Large-scale clinical trials have established that statin use for lowering blood cholesterol is beneficial in reducing atherosclerotic cardiovascular diseases in different populations. However, the general reputation of statins seems to be clouded by a potential adverse effect of a class of statins on glucose metabolism. This paper reviewed clinical data of statins regarding the effects on diabetes mellitus and glucose metabolism. At least five randomized controlled studies, primarily investigating the protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
3
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 28 publications
(21 reference statements)
5
54
3
8
Order By: Relevance
“…[1][2][3] Secondary diabetes outcomes in large cardiovascular statin trials of individuals without diabetes suggest that statin use can slightly raise the risk of developing diabetes, a fi nding we also confi rmed in this study with an eff ect size similar to those of randomised controlled trials. 6,7 Since worsening glycaemia is associated with microvascular disease, 18 individuals taking a statin after a diagnosis of diabetes might therefore be at increased risk of developing microvascular disease compared with those not taking a statin.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…[1][2][3] Secondary diabetes outcomes in large cardiovascular statin trials of individuals without diabetes suggest that statin use can slightly raise the risk of developing diabetes, a fi nding we also confi rmed in this study with an eff ect size similar to those of randomised controlled trials. 6,7 Since worsening glycaemia is associated with microvascular disease, 18 individuals taking a statin after a diagnosis of diabetes might therefore be at increased risk of developing microvascular disease compared with those not taking a statin.…”
Section: Discussionsupporting
confidence: 67%
“…However, fi ndings of some studies have shown that statin treatment might alter glucose metabolism, resulting in increased levels of glucose [1][2][3] and an increased risk for diabetes in individuals with one or more major risk factors for the disorder. [4][5][6][7] Nevertheless, whether statin use aff ects the development of microvascular disease in individuals with diabetes is presently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Sasaki et al have comprehensively reviewed the adverse effect of statins on glucose metabolism 7) . There are only a few relevant clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…2,10,27,29 In any event, the underlying mechanism explaining this deleterious effect is unclear, although it has been postulated that statin therapy may interfere with normal glucose metabolism and exacerbate glucose intolerance. 30,31 Statins are recommended for the management of hypercholesterolemia in the primary and secondary prevention of cardiovascular events in patients at risk. 10,[32][33][34][35] Given that diabetes has been considered a cardiovascular disease (CVD) risk equivalent, 36 the use of statins is strongly recommended in patients with diabetes or those at high risk of developing diabetes, including those with metabolic syndrome or prediabetes, 33 in whom CVD is highly prevalent and a common cause of death 19,37,38 ; statins have been shown to prevent cardiovascular events and reduce mortality in this population.…”
Section: Discussionmentioning
confidence: 99%